KORELASI ANTARA MOTIVASI BELAJAR DENGAN HASIL BELAJAR BIOLOGI KELAS X SMAS AL-HUSNIYAH - Desy Pitriyani; Arnentis Arnentis; Darmadi Darmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Research has been conducted which aims to determine the correlation between motivation to learn with biology learning outcomes SMAS AL-Husniyah. The research was conducted in class X IPA 3 SMAS AL-Husniyah maret-Oktober 2022. Research data collection was carried out by giving a set of statements to research respondents, then it was tasted on class X IPA 3 which consisted of 30 students. While for secondary data taken from midterm exam scores obtained through biology subject teachers. The research result werw used to determine the correlation between learning motivation and biology learning outcomes in class X SMAS AL-Husniyah. The correlation research stage is to test the validity and reliability, descriptive analysis, analysis of learning outcomes, correlation analysis and analysis of the coefficient of determination. The conclusion is that there is a signidicant correlation with the r count value 0,354 which is included in the medium category, this shows that there is a correlation between learning motivation and biology learning outcomes in class X SMAS AL-Husniyah.Key Words: Correlation, Motivation, Learning Outcomes